2004
DOI: 10.1177/0891241604266988
|View full text |Cite
|
Sign up to set email alerts
|

The Social Contexts of Focus Groups

Abstract: This article argues that focus group discussions are shaped by multiple social contexts, a fact that is often ignored by researchers. Using data from a focus group study of the effects of violence on everyday life, this article provides an analysis of four such contexts: the associational, status (especially gender), conversational, and relational contexts. These multiple and overlapping contexts foster both problematic silences (lack of disclosure) and problematic speech (strategic shaping of comments) in gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
311
0
28

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(353 citation statements)
references
References 42 publications
3
311
0
28
Order By: Relevance
“…The empirical data presented does not imply causality but provides a description of the relapse episode when it is managed successfully and is the basis for theories that need further examination. This study is based on a small number of persons not representative of the whole problem gambler population and is reported as part of a post hoc enquiry with its inherent problems of reporting bias (Hollander 2004). However, the strength of the study is that it presents a clear description of motivation for change; the 'pull' acting during the acute relapse process to maintain abstinence or urge reduction or extinction as ways of coping with the temptation to return to gambling.…”
Section: Discussionmentioning
confidence: 99%
“…The empirical data presented does not imply causality but provides a description of the relapse episode when it is managed successfully and is the basis for theories that need further examination. This study is based on a small number of persons not representative of the whole problem gambler population and is reported as part of a post hoc enquiry with its inherent problems of reporting bias (Hollander 2004). However, the strength of the study is that it presents a clear description of motivation for change; the 'pull' acting during the acute relapse process to maintain abstinence or urge reduction or extinction as ways of coping with the temptation to return to gambling.…”
Section: Discussionmentioning
confidence: 99%
“…27 However, we found that such potential drawbacks were outweighed by the opportunities that the group sessions offered us. Specifically, the unfolding group dynamics helped participants to explore and clarify their own perspectives, stimulated the exchange of experience in a relaxed atmosphere fostering mutual disclosure, and highlighted the values shared by patients who are at risk of medication misadventure.…”
Section: Study Limitationsmentioning
confidence: 95%
“…Le contexte de la tenue du groupe de discussion L'organisation de groupes de discussion focalisée nécessite que le chercheur tienne compte du contexte social de l'activité; ce contexte peut limiter l'apport de cette méthode pour connaître le point de vue, les sentiments ou l'expérience des participants (Hollander, 2004). Cet auteur identifie quatre contextes qui doivent être pris en considération : les contextes associé, statutaire, conversationnel et relationnel.…”
Section: La Durée De L'activitéunclassified